Pengembangan Hilirisasi Produk Berbasis Ekonomi Hijau dan Teknologi Digital Untuk Peningkatan Sosial Ekonomi Warga Desa Pasirbiru - Rahmi Rismayani Deri; Ganis Sanhaji; Noneng Nurhayani; Risfa Candra; Rohendro Junaedin (Politeknik Piksi Ganesha Indonesia, 2024)
Pasirbiru Village in Sumedang Regency has many residents below the poverty line, as well as quite a number who are stunted. This shows that residents do not have enough income to fulfill their daily needs and their families. Almost half of the residents are elementary school graduates who find it difficult to find decent work. Having an economically unproductive female population where housewives are 1,782 people or 35% of the female population of Pasir Biru Village, which if empowered can improve the socio-economy. The village produces sweet potatoes but has not been able to be properly downstreamed and the village does not yet have a superior product. Sweet potato plants are often attacked by plant pests, reducing the amount of harvest and the quality of the sweet potato. The Women Farmers Group (KWT) that was originally established cannot run well and tends to be passive because KWT does not have qualified knowledge, capital and entrepreneurial skills. Therefore, KWT through this community service is given pre-harvest training, post-harvest training, business management, digital marketing and building a special website for marketing downstream products in Pasirbiru Village. So that it can support the regional economy and become a developed village. Where from the measurement results of the training provided KWT can understand well and their skills increase.